Analisis Pengaruh Kualitas Produk, Harga, dan Promosi Terhadap Keputusan Pembelian Handphone Samsung pada Mahasiswa Kampus Negeri di Surakarta - Tiara Puri Wardani; Kun Ismawati (STIE Atma Bhakti, 2025)
The main objective of this research is to examine how the quality of a product, pricing strategies, and promotional efforts influence the purchasing preferences of Samsung mobile phones among students attending public universities in Surakarta. Elements such as product reliability, affordability, and the appeal of marketing campaigns are considered important factors in shaping consumer behavior when choosing Samsung devices. This study employs a quantitative approach and uses purposive sampling to select 100 respondents from state university students in Surakarta in 2025, specifically those who have experience using Samsung mobile phones. Data was collected through a structured questionnaire distributed via Google Forms to obtain accurate and relevant insights from the participants. To analyze the relationship between the independent variables (product quality, price, and promotion) and the dependent variable (purchase decision), the study applied multiple linear regression analysis, along with the F-test, t-test, and coefficient of determination (R²). The findings reveal that product quality and promotional efforts have a significant impact on consumers' purchase decisions, whereas pricing does not show a substantial influence.